Is the body condition of the invasive zebra mussel (Dreissena polymorpha) enhanced through attachment to native freshwater mussels (Bivalvia, Unionidae)? - Pilotto, Francesca (2016)
The invasion of zebra mussels, Dreissena polymorpha, into Western Europe and North America has driven widespread ecological change. Attachment of zebra mussels to the shell of native unionoid mussels has resulted in reductions in unionoid abundance and, in extreme cases, their localised extirpations. While the impacts of zebra mussels on infested unionoids are well documented, the possible benefits of the association to the zebra mussel have been little considered. We collected zebra mussels attached to unionoids and to inanimate structures. Zebra mussels attached to unionoids had significantly larger shells, higher standardized body mass and glycogen content than those attached to inanimate substrates, suggesting that D. polymorpha benefits from settling upon unionoids. The body condition of individual zebra mussels was negatively correlated with the number of zebra mussels attached to the unionoid, indicating intraspecific competition. Therefore, zebra mussels seem positively affected through attachment to unionoid mussels, but that these benefits decrease at higher densities of fouling. This association may offer advantages to the spread of zebra mussels within unionoid-rich systems, especially at sites with soft substrates and at the early stages of the invasion process where intraspecific competition is likely to be lower and benefits to the zebra mussels are higher.